The research of the importance of events for the development and branding of the city of Niš as a tourism destination - Marija Mandarić; Ivana Stamenković (Mенаџмент у хотелијерству и туризму, 2017)
Events play an important role in attracting tourists and have a strong effect on the tourism development, recognition of a tourism destination and the economic activity of a country. Branding may impact the creation of positive associations to the specific event and a positive image of a destination in order to attract more visitors. The paper analyzes the events in Niš, as well as the characteristics of the event tourism. The aim of the paper is to promote the importance and role of events for the development and branding of the city of Niš as a recognizable tourism destination, and, for this purpose, the field research was conducted. For the survey, the questionnaire was used. Based on the results of the survey, information is obtained on the motives and frequency of tourists‟ visits to cultural events, and the structure and level of visitors‟ satisfaction, with the possibility to point out the potential of the events for branding of the city of Niš as a distinctive tourism destination.